Application of The Principles of Equality and Non-Discrimination in Civil Law: Harmonization with International Legal Standards - Maria Yeti Andrias; Najamuddin Gani; Yulianus Poizon Aituru; Abdul Rahman Upara (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the application of the principles of equality and non-discrimination in Indonesian civil law as well as its harmonization with international legal standards. These principles form an essential foundation in protecting human rights and ensuring justice for all citizens without any discriminatory treatment. The research method used is normative, with a documentary study approach and comparative analysis of national legislation and related international legal instruments. The results show that although national legal norms have accommodated the principles of equality and non-discrimination, challenges in implementation still arise due to socio-cultural factors, limited understanding among legal officials, and a lack of regulations addressing modern discrimination issues. This study emphasizes the need to strengthen regulations, enhance the capacity of legal officials, and educate the public as efforts to effectively enforce these principles. A more progressive legal harmonization is expected to support the realization of social justice and human rights protection in Indonesia.